RoboPol: connection between optical polarization plane rotations and gamma-ray flares in blazars - D. Blinov; V. Pavlidou; I. Papadakis; S. Kiehlmann; I. Liodakis; G. V. Panopoulou; E. Angelakis; M. Balokovi´c; T. Hovatta; O. G. King; A. Kus; N. Kylafis; et al. (OXFORD UNIV PRESS, 2022)
We use results of our 3 yr polarimetric monitoring programme to investigate the previously suggested connection between rotations of the polarization plane in the optical emission of blazars and their gamma-ray flares in the GeV band. The homogeneous set of 40 rotation events in 24 sources detected by RoboPol is analysed together with the gamma-ray data provided by Fermi-LAT. We confirm that polarization plane rotations are indeed related to the closest gamma-ray flares in blazars and the time lags between these events are consistent with zero. Amplitudes of the rotations are anticorrelated with amplitudes of the gamma-ray flares. This is presumably caused by higher relativistic boosting (higher Doppler factors) in blazars that exhibit smaller amplitude polarization plane rotations. Moreover, the time-scales of rotations and flares are marginally correlated.